2019
DOI: 10.1080/02713683.2019.1623898
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Socioeconomic Factors, Lag Time, and High-Risk Histopathologic Features in Eyes Primarily Enucleated for Retinoblastoma

Abstract: Purpose/Aim: To determine the associations among socioeconomic factors, delay in management, and high-risk histopathologic features in eyes primarily enucleated for retinoblastoma. Materials and Methods: A single-Eyes primarily enucleated for unilateral retinoblastoma were reviewed for the presence of high-risk histopathologic features. Information on clinical characteristics, socioeconomic factors, and lag time were collected during hospitalization. Results: Of the 138 children analyzed, 60 (43.5%) carried hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
(16 reference statements)
2
17
1
1
Order By: Relevance
“…In the retinoblastoma cohort, delayed diagnosis longer than 2.5 months was an adverse prognostic factor, which is in agreement with the results of other studies [16,19]. Xiao et al [19] found that high-risk retinoblastoma had a longer interval from symptom presentation to enucleation than standard-risk retinoblastoma. According to Soliman et al [16], delayed diagnosis is significantly associated with advanced disease in both unilateral and bilateral retinoblastomas.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the retinoblastoma cohort, delayed diagnosis longer than 2.5 months was an adverse prognostic factor, which is in agreement with the results of other studies [16,19]. Xiao et al [19] found that high-risk retinoblastoma had a longer interval from symptom presentation to enucleation than standard-risk retinoblastoma. According to Soliman et al [16], delayed diagnosis is significantly associated with advanced disease in both unilateral and bilateral retinoblastomas.…”
Section: Discussionsupporting
confidence: 89%
“…According to Soliman et al [ 16 ], delayed diagnosis is significantly associated with advanced disease in both unilateral and bilateral retinoblastomas. Moreover, children with a delay of diagnosis longer than 30 days are at a significantly higher risk of extraocular invasion [ 19 ]. Early diagnosis in retinoblastoma is a key concern.…”
Section: Discussionmentioning
confidence: 99%
“…Such positive correlation between parent education and diseaserelated knowledge was also documented in other studies, such as in sleep disorders [14]. In retinoblastoma management, our former study indicated that higher parental education was associated with a shorter lag time of treatment [15]. Taken together, these findings suggest that emphasis should be made on less-educated parents when carrying out retinoblastoma specific educational campaigns.…”
Section: Discussionsupporting
confidence: 82%
“…The educational status was categorized into two groups: middle school and below; high school and above(13). Monthly household income was categorized into two levels: <3000 CNY (approximate 430 USD); ≥3000 CNY(14). In this cohort, there was no patient whose occupation was professor or semi-professor, thus occupational status was categorized into two levels: unemployed and employed(15).…”
Section: Methodsmentioning
confidence: 99%